Low-Volume Intense Exercise Elicits Post-exercise Hypotension and Subsequent Hypervolemia, Irrespective of Which Limbs Are Exercised - Graham, Matthew J.; Lucas, Samuel J. E.; Francois, Monique E.; Stavrianeas, Stasinos; Parr, Evelyn B.; Thomas, Kate N.; Cotter, James D. (Frontiers in Physiology, 2016)
Introduction: Exercise reduces arterial and central venous blood pressures during recovery, which contributes to its valuable anti-hypertensive effects and to facilitating hypervolemia. Repeated sprint exercise potently improves metabolic function, but its cardiovascular effects (esp. hematological) are less well characterised, as are effects of exercising upper versus lower limbs. The purposes of this study were to identify the acute (<24 h) profiles of arterial blood pressure and blood volume for (i) sprint intervals versus endurance exercise, and (ii) sprint intervals using arms versus legs. Methods: Twelve untrained males completed three cycling exercise trials; 50-min endurance (legs), and 5*30-s intervals using legs or arms, in randomised and counterbalanced sequence, at a standardised time of day with at least eight days between trials. Arterial pressure, hemoglobin concentration and hematocrit were measured before, during and across 22 h after exercise, the first 3 h of which were seated rest. Results: The post-exercise hypotensive response was larger after leg intervals than endurance (AUC: 7540 ± 3853 vs. 3897 ± 2757 mm Hg·min, p=0.049, 95% CI: 20 to 6764), whereas exercising different limbs elicited similar hypotension (arms: 6420 ± 3947 mm Hg·min, p=0.48, CI: -1261 to 3896). In contrast, arterial pressure at 22 h was reduced after endurance but not after leg intervals (-8 ± 8 vs. 0 ± 7 mm Hg, p=0.04, CI: 7 ± 7) or reliably after arm intervals (-4 ± 8 mm Hg, p=0.18 vs leg intervals). Regardless, plasma volume expansion at 22 h was similar between leg intervals and endurance (both +5 ± 5%; CI: -5 to 5%) and between leg and arm intervals (arms: +5 ± 7%, CI: -8 to 5%). Conclusions: These results emphasise the relative importance of central and/or systemic factors in post-exercise hypotension, and indicate that markedly diverse exercise profiles can induce substantive hypotension and subsequent hypervolemia. At least for endurance exercise, this hypervolemia may not depend on the volume of post-exercise hypotension. Finally, endurance exercise led to reduced blood pressure the following day, but sprint interval exercise did not.